AGW617 - Operations Strategy - August - September 1998 - PPP, Pusat Pengajian Pengurusan (1998)
UNIVERSITI SAINS MALAYSIA Master of Business Administration First Semester Examination Academic Session 1998/99 August/September 1998 AGW617 - Operations Strategy Time: [3 hours] Instructions: Please ensure that this examination paper contains FOUR (4) printed pages before you begin.